Interpersonal dynamics and relative positioning to scoring target of performers in 1 vs. 1 sub-phases of team sports - Esteves, P. T.; Araújo, D.; Davids, K.; Vilar, L.; Travassos, B.; Esteves, C. (Journal of Sports Sciences, 2012)
In this study, we examined the effects of relative positioning of attacker-defender dyads to the basket on interpersonal coordination tendencies in basketball. To achieve this aim, four right-hand dominant basketball players performed in a 1 vs. 1 sub-phase, at nine different playing locations relative to the basket (from 0° to 180°, in 20° increments). Performers` movement displacement trajectories were video-recorded and digitized in 162 trials. Results showed that interpersonal coordination tendencies changed according to the scaling of the relative position of performers to the basket.